PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L) PADA BERBAGAI POLA JAJAR LEGOWO DAN JARAK TANAM - Candra V. Donggulo; Iskandar M. Lapanjang; Usman Made (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
This study aimed to find the bestJajar Legowo system at different planting spaces for growth and yield of rice; to find Jajar Legowo system better for growth and yield of rice; and to find planting space better for growth and yield of rice.  The study used a Randomized CompletelyBlock design) with two factors including two kinds of planting spaces and three types of Jajar Legowo systems.  Each treatment combination had three replicates thus there were 18 experimental plots. The adoption of Jajar Legowo system of 2:1 at the planting space of 20 cm x 20 cm resulted in higher plant heights; similarlythe planting space of 25 cm x 25 cm at Jajar Legowo system of 3:1 produced higher plant heights.  The implementationof Jajar Legowo system of 4:1 had more tiller and panicle numbers per clump; whileJajar Legowo system 3:1 resulted in higher average grain weightwhich was 7.29 t/hacompared to the other Jajar Legowo system.Key Words :Jajar legowo, Planting space, Rice.